Influencing factors research on CHF at low pressure, low flow conditions in narrow channel based on Rough Set Decision Model. (March 2015) - Zhou, Tao; Yang, Xu; Fang, Xiaolu; Chen, Juan; Ju, Zhongyun; Xiao, Zejun
Highlights: This article is consistent with the theme of the thermal–hydraulic. It provides a new mathematical method for the analysis of the factors affecting the CHF (Critical Heat Flux). Also it has a great potential for research related to CHF. Abstract: CHF (Critical Heat Flux) is an important nuclear thermal–hydraulic parameter, and it is closely related to the reactor safety. Based on Rough Set Decision Model, this article proposed a new method to seek for the main factors which may affect CHF at low pressure, low flow conditions in narrow channels. Nine condition attributes are selected to build the CHF fault diagnosis model in narrow rectangular channels, and the rules of CHF occurring are obtained. These attributes include pipe diameter, circulating mode and flow stability, etc. The results show that flow instability could cause the CHF reach a minimum and CHF could be improved with the increase of pipe size. Diagnostic results in this method could predict the main influencing factors for CHF very well, and provide a new theoretical approach for the safety analysis of nuclear plants.